Analysis of Delay in Implementation of Work on Road Projects in Highways Division of Katingan Regency - Suta, Mey Midina; Prasetia, Irfan (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
ABSTRACT. This paper studied 21 road projects in Katingan Regency. In this research, nine factors were used, which were divided into 61 indicators that cause work delays. The analysis used in the research is descriptive analysis with index and variance analysis, which were previously tested for the validity and reliability of the questionnaire instrument. The research results show that 3 factors are very dominant in causing work delays, namely the equipment factor with indicators of delays in providing heavy equipment or delays in delivery or provision of equipment; material factors with indicators of delays in material delivery to the project location; and other factors with natural disaster indicators. Steps to minimize delays in work implementation are: holding periodic meetings; communicating and agreeing upon the critical path in order to obtain the most efficient and effective strategy; planning and scheduling the procurement of tools, materials, and labor in terms of purchasing, transportation, and delivery times; determining appropriate routes for transportation and delivery; determining the appropriate route and means of transportation for access to the project location to suit time and cost planning; as well as the readiness of supervisory consultants in the field to supervise contractor work methods. Keywords: Delays in Work Implementation, Delay Factors, Roads